Highly (E)-selective Wadsworth-Emmons reactions promoted by methylmagnesium bromide. - Claridge, T; Davies, S; Lee, J; Nicholson, R; Roberts, P; Russell, A; Smith, A; Toms, S (2008)
An experimentally simple protocol for the very highly (E)-selective Wadsworth-Emmons reaction [(E):(Z) selectivities in excess of 180:1 in some cases] of a range of straight-chain and branched aliphatic, substituted aromatic, and base-sensitive aldehydes via reaction with an alkyl diethylphosphonoacetate and MeMgBr is reported.